Accumulation of 8-hydroxydeoxyguanosine, L-arginine and Glucose Metabolites by Liver Tumor Cells Are the Important Characteristic Features of Metabolic Syndrome and Non-Alcoholic Steatohepatitis-Associated Hepatocarcinogenesis - Kakehashi, Anna (Int J Mol Sci, 2020)
To uncover mechanisms and explore novel biomarkers of obesity, type 2 diabetes (T2DM) and nonalcoholic steatohepatitis (NASH)-associated hepatocarcinogenesis, cellular and molecular alterations in the liver, and hepatocellular carcinomas (HCCs) were investigated in NASH model 60-week-old Tsumura, Suzuki, Obese Diabetic (TSOD) mice and NASH HCC patients. Markedly elevated lipid deposition, inflammation, fibrosis, and peroxisome proliferation in the liver, preneoplastic lesions, and HCCs of TSOD mice were accompanied by accumulation of polysaccharides in the cellular cytoplasm and nuclei and increase of oxidative DNA damage marker, 8-hydroxydeoxyguanosine (8-OHdG) formation in the liver and altered foci. Metabolomics of TSOD mice HCCs demonstrated significant elevation of the concentration of amino acid L-arginine, phosphocreatine, S-adenosylmethionine/S-adenosylhomocysteine ratio, adenylate, and guanylate energy charges in coordination with tremendous rise of glucose metabolites, mostly fructose 1,6-diphosphate. L-arginine accumulation in HCCs was associated with significant under-expression of arginase 1 (ARG1), suppression of the urea cycle, methionine and putrescine degradation pathways, activation of Ser and Thr kinase Akt AKT, phosphoinositide 3-kinase (PI3K), extracellular signal-regulated kinase 1/2 (ERK1/2) kinases, β-catenin, mammalian target of rapamycin (mTOR), and cell proliferation. Furthermore, clinicopathological analysis in 20 metabolic syndrome/NASH and 80 HCV-positive HCC patients demonstrated significant correlation of negative ARG1 expression with poor tumor differentiation, higher pathological stage, and significant decrease of survival in metabolic syndrome/NASH-associated HCC patients, thus indicating that ARG1 could become a potential marker for NASH HCC. From these results, formation of oxidative stress and 8-OHdG in the DNA and elevation of glucose metabolites and L-arginine due to ARG1 suppression in mice liver cells are the important characteristics of T2DM/NASH-associated hepatocarcinogenesis, which may take part in activating oxidative stress resistance, synthesis of phosphocreatine, cell signaling, methylation, and proliferation.